If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 = 3x + 9 Reorder the terms: 4 + -2x = 3x + 9 Reorder the terms: 4 + -2x = 9 + 3x Solving 4 + -2x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -2x + -3x = 9 + 3x + -3x Combine like terms: -2x + -3x = -5x 4 + -5x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + -5x = 9 + 0 4 + -5x = 9 Add '-4' to each side of the equation. 4 + -4 + -5x = 9 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 9 + -4 -5x = 9 + -4 Combine like terms: 9 + -4 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| (3/3)*(3/3) | | -4(1x+1)+6x=2(1x+2)-8 | | h(x)=4.9X^2+2x+3 | | 5(g-7)+2[g-3g(g-5)]=0 | | -2(5t-2)+8t=7t-9 | | 6*x=2/3 | | 6x^2+4=3x | | 4(x+12)+5x=9x-48 | | 2x-3(5)=-9 | | 5(6-7)+2[g-3(g-5)]=0 | | w/2-11=9 | | 6+6(2+x)=-5x+6(x+8+5) | | x+53=45+2x | | 0.15(y-5)+0.39y=0.04y-0.50 | | X+(1+x)+(2+x)=51 | | 9k-z=43 | | -6(r+.2)=1.8 | | X^4+2x^2y^2+9y^4= | | -15-2=-5 | | 3x(x-5)-(x+5)=0 | | 1/2=11.7/x | | 6y-17=-23 | | 6x+7=7x-11 | | 4/3(2x-1)=-12(-4) | | 6+7m=8m | | -8b+q=s | | 3(-4.5+1.5y)-y=4 | | 3(1u-2)+5=2(3u-5) | | 3ln(11/X) | | 27x^4-208x^3-64=0 | | X+x+n=18 | | 4x+2y=10-4x |